Determining the Impact of Capital Flight on Economic Growth and Financial Stability in Palestine - Badwan, Nemer (New Innovations in Economics, Business and Management Vol. 6, 2022)
This study looked at the impact of capital flight on economic growth and Financial Stability in Palestine from the period (2000-2020). The study made use of time-series data on capital flight, foreign exchange reserves, foreign debt, and real GDP, as well as ordinary least squares estimation technology to analyse the research data. Johansen co-integration and error correction mechanism was used. The research findings indicate that there is a co-integration relationship between the research variables, and capital flight has harmed the Palestinian case's economic growth. Based on the results, the study suggests that the government create a favourable investment environment in order to encourage investment and prevent capital flight from Palestine. Furthermore, because these infrastructure projects/programs will lower the country's production costs, the Palestinian government should prevent capital flight. The government should create an appropriate investment environment for foreign investment and encourage entrepreneurs and equity owners to invest these funds in the domestic market. Furthermore, the government should direct all foreign aid funds to appropriate areas in order to boost economic growth and create job opportunities for the unemployed, thereby raising the national economic growth rate.